Logics in Computer Science A Study on Extensions of Temporal and Strategic Logics - Mogavero, Fabio; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2013)
In this monograph we introduce and examine four new temporal logic formalisms that can be used as specification languages for the automated verification of the reliability of hardware and software designs with respect to a desired behavior. The work is organized in two parts. In the first part two logics for computations, the graded computation tree logic and the computation tree logic with minimal model quantifiers are discussed. These have proved to be useful in describing correct executions of monolithic closed systems. The second part focuses on logics for strategies, strategy logic and memoryful alternating-time temporal logic, which have been successfully applied to formalize several properties of interactive plays in multi-entities systems modeled as multi-agent games.
Graded Computation Tree Logic -- Minimal Model Quantifiers -- Reasoning About Strategies -- Relentful Strategic Reasoning -- Appendix A Mathematical Notation.
Keywords: Computer science; Computer software; Logic design; Computer Science; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Algorithm Analysis and Problem Complexity